Council of the 265th session (Res Medica, 2014)
RMS Council. 265th session. 2001-02, Senior President: Katherine Paramore, 1st Junior President: Timothy Andrews, 2nd Junior President: Kirsteen Moreland, 3rd Junior President: David Cavanagh.